Congrong Shujing Granule-Induced GRP78 Expression Reduced Endoplasmic Reticulum Stress and Neuronal Apoptosis in the Midbrain in a Parkinson's Disease Rat Model. (1st October 2020) - Xu, Qian; Yang, Shasha; Wu, Fangzhen; Lin, Yao; Zhong, Jianan; Tang, Lanfang; Hu, Xuefeng; Cai, Jing
Abstract : The main pathological changes inherent in Parkinson's disease (PD) are degeneration and loss of dopamine neurons in the midbrain and formation of Lewy bodies. Many studies have shown that the pathogenesis of PD is closely related to endoplasmic reticulum (ER) oxidative stress. This study combined various traditional Chinese medicines to prepare Congrong Shujing granules (CSGs). The optimal dose combination of the ingredients was identified by experimental intervention in SH-SY5Y cells in vitro . A PD rat model was established by intraperitoneal injection of rotenone sunflower oil emulsion. The suspension tests were performed on the 14th day after modeling and also on the 14th day after CSG intervention (5.88 g/kg, 11.76 g/kg, and 23.52 g/kg). We evaluated the changes in motor function and the expression of neuronal cell functional marker proteins, ER stress (ERS) marker proteins, and apoptosis-related pathway proteins of neuronal cells. Changes in cellular ultrastructure were observed by electron microscopy. Our results showed that CSG treatment lengthened the duration of PD rats' gripping to the wire. 78 kDa glucose-regulated protein (GRP78) expression in the substantia nigra was significantly upregulated in the middle- and high-dose CSG groups after 14 days of treatment compared with the model group. The expression of the key dopaminergic neuron functional enzyme tyrosine hydroxylase (TH) and cerebral dopamine neurotrophic factor (CDNF) was elevated. The expression of c-Jun N-terminal kinase (JNK) and phosphorylated c-Jun decreased, and cell apoptosis was significantly reduced. Compared with the model group, the treatment groups had fewer ER fragmentation and degranulation (ribosome shedding) and abundant ER and mitochondria suggesting that CSG reduced ER stress and neuronal apoptosis in the midbrain of a PD rat model by inducing the expression of molecular chaperone GRP78.